In bloom: Gender differences in preferences among adolescents - Anna Dreber; Emma von Essen; Eva Ranehill (Stockholm School of Economics, The Economic Research Institute (EFI), 2011)
We look at gender differences in preferences for altruism, risk and competition in math and word search among adolescents in Sweden. We find that girls are more altruistic and less risk taking than boys. We find no gender gap in performance change when comparing performance under non-competition with performance under competition. Boys and girls are equally likely to choose to compete in word search, but boys are significantly more likely to choose to compete in math. However, this gender gap diminishes and becomes non significant when we control for relative performance beliefs, indicating that some of the gender gap in our sample is not due to competition preferences per se.
Keywords: C91; D03; J16; 330; competitiveness; risk preferences; altruism; adolescents; gender differences; experiment; Wettbewerb; Risikopräferenz; Altruismus; Mathematik; Jugendliche; Geschlecht; Test; Schweden